Analisis Emosi Presiden Donald Trump Terhadap Penarikan diri Amerika Serikat dari Paris Agreement - Irene F Sinaga; Mohamad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
USA was one of its parties who signed Paris Agreement on the first date it was open for signature. Nevertheless, the euphoria of leading the world by example could not last longer. It happened when Donald Trump was inaugurated as the 45th President of the US on January 2017, succeeding Barack Obama. He announced that US would withdraw from the Paris climate accord. With his announcement, President Trump has snubbed the international climate policy community, also confused numerous world leaders and civilians across the world. Previous article journals on US withdrawal from the accord mostly focused on the national interest of US, and effects of the US withdrawal from Paris Agreement on the accord. In the present paper, authour would find another factor behind influencing Trump’s decision to quit from the accord connected emotion theory. Researcher argues that Trump’s emotion specifically his anger is one of the factors that influences US quit from the Paris Agreement.